The message of Esther : God present but unseen - Firth, David G. (Downers Grove, Ill. : Inter-Varsity Press, 2010)
In this volume in the Bible Speaks Today commentary series, David Firth explores this paradoxically important book and its implications for our own contemporary context, where the reality of God's presence is experienced against a backdrop of God's relative anonymity and seeming absence. --From publisher's description.
Some parties and their aftermath (1:1-22) -- Providence in the passive voice (2:1-23) -- Power and corruption in high places (3:1-15) -- Risking all (4:1-17) -- A tale of two banquets (5:1-14) -- A funny thing happened (6:1-13) -- An awkward dinner (6:14 - 7:10) -- Revoking the irrevocable (8:1-17) -- Days of deliverance (9:1-19) -- Remembering deliverance (9:20-10:3).
Includes bibliographical references.
Keywords: Bible. -- Commentaries